KUALITAS PRODUK DAN KUALITAS PELANAN SEBAGAI ANTASEDEN KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN (Studi Pada Pelanggan Waroeng Spesial Sambal â€œSSâ€ Cabang Veteran Yogyakarta) - Alo Rahmawati Mulyana; Hendro Setyono (Universitas Ahmad Dahlan, 2019)
Â The aim of study is toÂ analyze about effectÂ productÂ qualityÂ andÂ serviceÂ qualityÂ on customerâ€™s satisfaction to build customerâ€™s loyalty at Waroeng Spesial Sambal â€œSSâ€ in the branch of Veteran Yogyakarta. Population in this study are all consumers who makeÂ purchases at Waroeng Spesial Sambal â€œSSâ€ the branch in theÂ branch of Veteran Yogyakarta. While the sampleÂ inÂ thisÂ studyÂ is a portion of consumers who haveÂ made Â purchases at least twice in the past year. The sampling technique uses purposive sampling. The dataÂ used in this study is primary data. The numberÂ of studiesÂ inÂ thisÂ study wereÂ sixtyÂ samplesÂ inÂ theÂ city of Yogyakarta whichÂ were processedÂ usingÂ multiple linear regressionÂ analysisÂ and mediation analysisÂ using SPSS 20 for windows. The results of the analysis in this study are: product quality dosenâ€™t have a significant effect on customer satisfaction,Â service quality has a significant effect on customer satisfaction, customer satisfaction doesnâ€™t have a significant effect on customer loyalty, product qualityÂ dosenâ€™tÂ have a significantÂ effect onÂ customer loyalty and service quality has a significant effect on customer loyalty of the two independentvariables dosenâ€™t indicate a mediatingÂ relationshipÂ with Â customerÂ satisfaction as a mediator variable.